Maternal Healthcare Utilization and Health-Related Quality of Life among Young Pregnant Mothers Aged 10-24 Years in Eastern Uganda: A Cross-sectional Study - Joan, Nakkazi; Musoke, Miph; Nanyingi, Miisa; Pio Kiyingi, Frank; Martin, Odoki (International Journal of Global Health, 2026)
Introduction Young pregnant mothers experience heightened biological, social, and economic vulnerabilities that may compromise health-related quality of life (HRQoL), especially in low-resource settings. Although maternal healthcare service utilization (MHCSU) improves clinical outcomes, evidence linking it to HRQoL among young mothers in Uganda remains limited. This study examined determinants of HRQoL among young pregnant mothers aged 10–24 years in Eastern Uganda, with emphasis on MHCSU. Methods A cross-sectional analytical study was conducted among 967 young pregnant mothers in selected districts of Eastern Uganda. The study used baseline data collected prior to randomization and implementation of any intervention. Although the WHOQOL-BREF instrument was administered in full, the present analysis utilized the global quality-of-life item (Question 1: "How would you rate your quality of life?") as the primary outcome measure. Responses ranged from very poor (1) to very good (5) and were analyzed as an ordinal outcome using ordered logistic regression. Data were analyzed using descriptive statistics, ANOVA for bivariate associations and ordered logistic regression models to assess predictors of HRQoL, all conducted at a 95% confidence level. Results Results from the bivariate analysis indicated that uptake of antenatal care (ANC), skilled birth attendance (SBA), and access to postnatal care (PNC) were associated with better health-related quality of life (HRQoL) among young pregnant mothers. Mothers who attended antenatal care reported higher mean HRQoL scores compared to those who did not (2.98 ± 1.12 vs. 2.66 ± 0.96, p = .001), demonstrating that ANC utilization is positively linked to maternal well-being. Similarly, mothers who delivered with the assistance of skilled birth attendants had higher HRQoL scores than those who did not (3.00 ± 1.11 vs. 2.65 ± 0.97, p < .001), indicating the importance of skilled delivery care in improving quality of life. Access to postnatal care also showed a positive association, with mothers who received PNC services reporting higher HRQoL scores compared to those who did not (2.97 ± 1.12 vs. 2.71 ± 1.10, p = .003). Overall, these findings suggest that increased utilization of maternal healthcare services is consistently associated with improved HRQoL among young pregnant mothers. In the ordered logistic regression analysis, ANC uptake remained a statistically significant predictor of HRQoL (OR = 1.686, p < .001), indicating that mothers who accessed ANC services had approximately 1.69 times higher odds of being in better quality of life categories compared to those who did not. Similarly, skilled birth attendance was positively and significantly associated with HRQoL (OR = 1.761, p < .001), suggesting that mothers who delivered with skilled health personnel were more likely to report improved quality of life outcomes. Access to postnatal care also demonstrated a significant positive effect (OR = 1.552, p = .002), implying that mothers who received PNC services had higher odds of better HRQoL. In the multivariable model, immediate health-seeking behavior remained a significant predictor (OR = 1.411, p = .006), indicating that prompt care utilization increases the likelihood of improved well-being. Conversely, perceived quality of care was negatively associated with HRQoL; compared to mothers who perceived care as excellent, those who rated care as good (OR = 0.394, p < .001), fair (OR = 0.083, p < .001), and poor (OR = 0.077, p < .001) had significantly lower odds of reporting better quality of life. These findings highlight the critical importance of perceived care quality in shaping maternal well-being. Conclusion Maternal healthcare service utilization and positive care experiences were significantly associated with better HRQoL among young pregnant mothers. Expanding access to ANC, SBA, and PNC alongside respectful, youth-responsive care is essential to improve maternal well-being in Eastern Uganda.
Keywords: Determinants; health-related quality of life; young pregnant mothers; maternal healthcare service utilization; antenatal care; skilled birth attendance; postnatal care; maternal health; Uganda